Profile of Self Help Groups (SHGs) and their Members Engaged in Pig Rearing Activity in Mizoram - Hmingthanzuala,; Das, Samares Kumar; Rahman, Saidur; Tolenkhomba, T. C.; Saikia, Prasanta (International Journal of Bio-resource and Stress Management, 2016)
Self Help Groups (SHGs) have shown the way for the poor. Impressed by the success of women SHGs in Andhra Pradesh, the World Bank recommended replicating the model in other states in India. In Mizoram, the strength of SHGs is ever growing with the initiative taken by government agencies such as National Bank for Agriculture and Rural Development (NABARD), District Rural Development Agency (DRDA), etc. However, there is a dearth of studies on SHGs in Mizoram. Present study was undertaken in the district of Serchhip and Kolasib of Mizoram where the National Rural Livelihood Mission (NRLM) had been forming SHGs around piggery since 2012. The objective was to study the socio-economic profile of SHGs and their members. Profile of SHGs included age, members and their type, group activities (savings, internal lending, group meeting, election, and training). Profile of members included age, education, occupation, income, family size, land holding, experience in piggery, and herd size. The study concludes that SHG can be promoted among young and old. Members were literate which was an advantage. Pig rearing as a SHG activity was compatible to the society. Members joined to form Joint Liability Group (JLG). There was a scope for the government agencies to involve in the formation of SHGs. There is a need to study the relationship between profile of SHGs and their members, and the sustainability of SHGs.